2010
DOI: 10.1167/iovs.09-4894
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning with Inhalative Carbon Monoxide Protects Rat Retinal Ganglion Cells from Ischemia/Reperfusion Injury

Abstract: PURPOSE. Retinal ischemia/reperfusion (I/R) injury damages retinal neurons. Carbon monoxide (CO) recently attracted attention as cytoprotective because of its anti-inflammatory and antiapoptotic effects. Rapid preconditioning of retinal neurons by inhaled CO before I/R injury may reduce inflammation and apoptosis in retinal ganglion cells (RGCs). METHODS. I/R injury was performed on the left eyes of rats (n = 8) with or without inhaled CO preconditioning (250 ppm) for 1 hour before ischemia. Densities of fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 56 publications
7
58
1
Order By: Relevance
“…Nitric oxide (NO) is generated by iNOS-induced delayed neuronal cell death after ischemia (Samdani et al, 1997). It had been reported that the activation of NF-kB is associated with an increased expression of these inflammatory mediators after I/R injury (Dvoriantchikova et al, 2009a(Dvoriantchikova et al, , 2009bGustavsson et al, 2008;Biermann et al, 2010). In this study, we clearly demonstrated that COS could inhibit NF-kB activation and decrease the expression of IL-1b, TNF-a, MCP-1, iNOS and ICAM-1.…”
Section: Discussionsupporting
confidence: 49%
“…Nitric oxide (NO) is generated by iNOS-induced delayed neuronal cell death after ischemia (Samdani et al, 1997). It had been reported that the activation of NF-kB is associated with an increased expression of these inflammatory mediators after I/R injury (Dvoriantchikova et al, 2009a(Dvoriantchikova et al, , 2009bGustavsson et al, 2008;Biermann et al, 2010). In this study, we clearly demonstrated that COS could inhibit NF-kB activation and decrease the expression of IL-1b, TNF-a, MCP-1, iNOS and ICAM-1.…”
Section: Discussionsupporting
confidence: 49%
“…By contrast, retinas with RIR injury experienced severe cell death in the GCL 7 days after reperfusion, which was in accordance with previous studies (22,23). Treatment with HRS significantly decreased the number of TUNEL-positive cells in the GCL of RIR rats on the seventh day after reperfusion (P<0.001), suggesting that HRS may have a protective effect on cell apoptosis (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Prior to this understanding, there was controversy over the incontrovertible toxicity of the gas versus observations supporting low dose CO as a cell protectant operating through general anti-inflammatory and antiapoptotic properties (Ryter et al, 2006;Suliman and Piantadosi, 2014). Indeed, many protective effects of HO-1 induction by ischemia, hypoxia, oxidative stress, metals, and inflammation are not simply due to heme clearance and in many cases can be recapitulated by CO administration (Maines, 2005;Vieira et al, 2008;Biermann et al, 2010;Lee et al, 2014).…”
Section: B the Heme Oxygenase-1/carbon Monoxide Systemmentioning
confidence: 99%